Attitudes, experiences, and barriers to research and publishing among dental postgraduate students of Bengaluru City: A cross-sectional study - Aditi Hegde; Gopikrishna Venkataramana; Smitha B Kulkarni; Nithin N Bhaskar; Jeswin Jacob; Sourabha K Gangadharappa (Wolters Kluwer Medknow Publications, 2017)
Background: Research experience not only enhances understanding but also instills evidence-based practice and improves skills. A natural successor to research is academic publishing. Unfortunately, student research itself is plagued by a number of barriers. Aim: To identify the attitudes, experiences, and barriers to research and publishing among dental postgraduate students of Bangalore city. Materials and Methods: A cross-sectional survey using purposive sampling technique was conducted among the dental postgraduate students of all specialties in Bengaluru city in the months of July-August 2015. A prevalidated, close-ended, self-administered questionnaire consisting of 26 questions was used. Data from 638 completed questionnaires were entered into and analyzed using Microsoft Excel 2013 and SPSS software version 14. Results: The majority of the students displayed a positive attitude towards research and stated that they would like more opportunities to take part in research (89%). Most students were positive toward publishing research; 94% agreed that it is important to publish, although only 43.7% had submitted an article for publication. The single most often stated barrier to conducting research was a lack of funding from the institution (15.7%), followed by workload and time constraints (15.0%). Lack of training and good mentorship was the most often (23.3%) faced barrier to publishing, along with high publication fee for indexed journals (17.9%). Conclusion: Dental postgraduate students show an urge to conduct research and publish their results. Research-related workshops for teachers and students are suggestions for improving the status of research in dental colleges.